THE IMPLEMENTATION OF MATRIX SWOT STRATEGY WITHIN THE ELABORATION OF THE VISION AND MISSION AT THE PRIVATE COLLEGES IN BOGOR AND SUKABUMI (This Research Has Been Done at Binaniaga Economics College Bogor, Binaniaga Computer Science College Bogor, Academy of Computer and Information Management Bogor, and BBC Polytechnique Sukabumi) - Ismulyana Djan (STIE Binaniaga, 2017)
This research aims to make the vision and mission created by the college come true refers to the job program of each authority person and executor applying SWOT (Threats, Opportunities, Weaknesses, Strengths) matrix strategy. The research based on the implementation of the theory determined which has been applied practically obtaining the vision and mission that should have to be elaborated accordingly which is in compliance with the mechanism of the theory completed and integrated. Elaborating the vision and mission to achieve the objectives, goals and strategy as well as a clear job program of the college as the guideline for the people in charge to perform their duties accordingly refers to the budget, scope of the responsibility, coordination with their superior due to the time-line of their duties.Keyword: SWOT Matrix